DESTINATION SUCCESSES FACTORS FOR MILLENNIAL TRAVELERS CASE STUDY OF TANAH LOT TEMPLE, TABANAN, BALI - Pramono, Jaya; Sumartana, I Made; Santosa, I Made; Denny Herlambang, Putu Gede; Purwantoro, Bambang (ADI Journal on Recent Innovation, 2020)
Millennials are a popular term to replace the term Generation Y (Gen Y). There are 2.5 billion millennials worldwide. They have contributed to business travel, and tend to spend most of their expenses on travel and vacation, driven by future travel trends. This research conducted to shape the success factor of the destination for millennial tourists, where the destination of Tanah Lot Temple is used as a case study, which is quantitative research, using survey design and purposive sampling. There are 160 millennial tourists as respondents (who are visited Tanah Lot Temple). The instrument used was a questionnaire with a Likert scale, and the data were analysed using descriptive statistics and factor analysis. This research has indicated that there are nine (9) main factors that shape the success factor of the destination for millennial tourists. The nine main factors are: Millennials interested in traditional costume guides and officers, believe in social media reviews, Millennial will add several/more days to enjoying the destination, The layout of the souvenir shop, buildings, temples, parks, and the others building should support sustainable practices. A millennial will invite parents and closest friends for visiting destination. The experience in destination worth it with or even more than spending, and meet the expectations. The facility of destination affected millennials during visiting. Millennials are interested in the culture at the destination. Traveling is a necessity for Millennial. This research model has an accuracy of 71% on the error rate of 5%.